A multiscale computational fluid dynamics approach to simulate the micro-fluidic environment within a tissue engineering scaffold with highly irregular pore geometry - Feihu Zhao (Biomechanics and Modeling in Mechanobiology, 2019)
Mechanical stimulation can regulate cellular behavior, e.g., differentiation, proliferation, matrix production and mineralisation. To apply fluid-induced wall shear stress (WSS) on cells, perfusion bioreactors have been commonly used in tissue engineering experiments. To gain a better insight into the actual mechanical stimulation on cells in a tissue engineering experiment, computational simulation of the fluidic environment within scaffolds is important. However, biomaterial scaffolds typically have extremely complex geometries. This implies high computational costs for simulating the precise fluidic environment within the scaffolds. In this study, we propose a low-computational cost and feasible technique for quantifying the micro-fluidic environment within the scaffolds, which have extremely complex (or highly irregular) geometries. This technique is based on a multiscale computational fluid dynamics approach. The validation results have demonstrated that this approach can capture the WSS distribution in most regions within the scaffold. Importantly, the central process unit time needed to run the model is considerably low.